Ureteroarterial Fistula from Ureteral Stump: A Challenging Case. (13th November 2014) - Pozzilli, Pietro; Lenti, Massimo; Mosca, Stefano; Nunzi, Elisabetta; Mearini, Luigi
Abstract : Ureteroarterial fistula (UAF) is a relatively rare condition with about 150 cases reported in the literature. Since it is a potentially life-threatening condition, a prompt diagnosis and treatment are crucial. We present here a rare, challenging case of UAF diagnosed after left nephrectomy, thus involving the ureteral stump. The difficult diagnosis and treatment by contemporary use of endovascular stent placement and ureteral occlusion by mean of metallic coils and Onyx injection are discussed.